(untitled) (European Journal of Pure and Applied Mathematics, 2023)
In this paper we define new types of bipolar fuzzy ideals, bipolar fuzzy almost ideals in Γ-semigroups. We discussed properties of bipolar fuzzy ideals, bipolar fuzzy almost ideals, minimal bipolar fuzzy ideal, minimal bipolar almost ideal in Γ-semigroups. Moreover, we prove connection between almost ideals and bipolar fuzzy almost ideals of Γ-semigroups.